2012
DOI: 10.1007/s00408-012-9371-2
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Promoter Polymorphism is Associated with Risk of Malignant Mesothelioma

Abstract: The findings of this study suggest that long (GT)n repeats in the HO-1 gene promoter are associated with a higher risk of malignant mesothelioma in the Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Several genetic studies have been carried out to assess the association between HO-1 gene polymorphism and the risk of cancer in humans [ 15 - 23 ]. It has been shown that subjects carrying the shorter (GT) repeats have lower risk in oral squamous cell carcinoma [ 15 ], lung adenocarcinoma [ 16 ], gastric adenocarcinoma [ 18 ], breast cancer [ 19 ], esophageal squamous cell carcinoma [ 21 ], and malignant mesothelioma [ 23 ]. However, some reported the higher risk for melanoma [ 17 ], gastric cancer [ 20 ], and pancreatic cancer [ 22 ] in subjects carrying the shorter repeats.…”
Section: Reviewmentioning
confidence: 99%
“…Several genetic studies have been carried out to assess the association between HO-1 gene polymorphism and the risk of cancer in humans [ 15 - 23 ]. It has been shown that subjects carrying the shorter (GT) repeats have lower risk in oral squamous cell carcinoma [ 15 ], lung adenocarcinoma [ 16 ], gastric adenocarcinoma [ 18 ], breast cancer [ 19 ], esophageal squamous cell carcinoma [ 21 ], and malignant mesothelioma [ 23 ]. However, some reported the higher risk for melanoma [ 17 ], gastric cancer [ 20 ], and pancreatic cancer [ 22 ] in subjects carrying the shorter repeats.…”
Section: Reviewmentioning
confidence: 99%
“…No association between the various single nucleotide polymorphisms of HO-1 and lung function decline could be found, nor was there any evidence that three promoter polymorphisms affected the regulation of HO-1 gene (101). In 44 asbestos-exposed subjects without mesothelioma and 78 asbestos-exposed subjects with mesothelioma, long GT repeats were significantly higher in the asbestos-exposed subjects with mesothelioma, suggesting that decreased induction of HO-1 is associated with a higher risk of malignant mesothelioma (68). In 749 French subjects aged 20-44, lung function was assessed and compared with the length of HO-1 promoter polymorphisms.…”
Section: Multiple Roles Of Ho-1 In Angiogenesis and Vascular Prolifermentioning
confidence: 99%
“…Numerous studies have demonstrated that the LL genotype of the HO-1(GT)n locus may increase cancer susceptibility ( 12 , 13 , 16 , 18 , 19 , 21 ). However, the associations identified between the HO-1 polymorphisms and cancer susceptibility are inconsistent, and other studies have come to other conclusions ( 15 , 17 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, ROS may modulate tumorigenesis by causing cell apoptosis/necrosis or an accumulation of DNA damage ( 11 ). Two loci of the HO-1 gene have been focused on when regarding its potential association with cancer, namely the (GT)n repeat length polymorphism [which according to repeat length is divided into two classes: S (short) and L (long)] and T(−413)A (rs2071746) ( 12 14 ); however, results so far are not conclusive. Both loci are localized on chromosome 22q12 and have been identified in the HO-1 gene promoter region ( 15 ).…”
Section: Introductionmentioning
confidence: 99%